Neuroprotective effects of Gypenosides: a review on preclinical studies in neuropsychiatric disorders - Liang, Gengfan; Lee, Yu Zhao; Siew, Audrey Foong Kow; Lee, Qi Long; Cheng Lim, Luis Wei; Yusof, Rohana; Tham, Chau Ling; Ho, Yu Cheng; Lee, Ming Tatt (Elsevier B.V., 2024)
Gynostemma pentaphyllum (Thunb.) Makino is a perennial creeping herb belonging to the Cucurbitaceae family that has a long history of usage in traditional oriental medicine. Gypenosides are the primary bioactive compounds in Gynostemma pentaphyllum. Because of the medicinal value of gypenosides, functional food and supplements containing gypenosides have been promoted and consumed with popularity, especially among Asian communities. This review presented the progress made in the research of pharmacological properties of gypenosides on diseases of the nervous system and their possible mechanism of action. To date, preclinical studies have demonstrated the therapeutic effects of gypenosides in alleviating neuropsychiatric disorders like depression, Parkinson’s disease, Alzheimer’s disease, secondary dementia, stroke, optic neuritis, etc. Pharmacological studies have discovered that gypenosides can modulate various major signaling pathways like NF-κB, Nrf2, AKT, ERK1/2, contributing to the neuroprotective properties. However, there is a dearth of clinical research on gypenosides, with current investigations on the compounds being mainly conducted in vitro and on animals. Future studies focusing on isolating and purifying novel gypenosides and investigations on exploring the potential molecular mechanism underlying their biological activities are warranted, which may serve as a foundation for further clinical trials for the betterment of human health.